2009
DOI: 10.1016/j.cell.2009.06.045
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Removal of Ribosome Biogenesis Factors from Nascent 60S Ribosomal Subunits

Abstract: The dynein-related AAA ATPase Rea1 is a preribosomal factor that triggers an unknown maturation step in 60S subunit biogenesis. Using electron microscopy, we show that Rea1's motor domain is docked to the pre-60S particle and its tail-like structure, harboring a metal ion-dependent adhesion site (MIDAS), protrudes from the preribosome. Typically, integrins utilize a MIDAS to bind extracellular ligands, an interaction that is strengthened under applied tensile force. Likewise, the Rea1 MIDAS binds the preriboso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
292
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(301 citation statements)
references
References 36 publications
8
292
0
1
Order By: Relevance
“…This phase is also marked by the association of the Rix1 subcomplex and the AAA-ATPase Rea1 [21,33,99] (Figures 2N and 5). Interestingly, the interaction between Rix1 and Rea1 may be regulated, as indicated by a recent study with the orthologous human proteins showing that their association is controlled by a dynamic SUMO conjugation/deconjugation cycle [100].…”
Section: Assembly Of the Lsumentioning
confidence: 90%
See 2 more Smart Citations
“…This phase is also marked by the association of the Rix1 subcomplex and the AAA-ATPase Rea1 [21,33,99] (Figures 2N and 5). Interestingly, the interaction between Rix1 and Rea1 may be regulated, as indicated by a recent study with the orthologous human proteins showing that their association is controlled by a dynamic SUMO conjugation/deconjugation cycle [100].…”
Section: Assembly Of the Lsumentioning
confidence: 90%
“…Subsequently, the purification of additional preribosomal particles provided a detailed spatiotemporal picture of the preribosomal intermediates and their composition [5,9,14] (Figure 2). A few of these preribosomal particles were visualized at relatively low resolution by EM [21][22][23][24]. Recent progress in cryo-EM has enabled a quantum jump by permitting the visualization of preribosomal particles at atomic or near-atomic resolution [25][26][27][28][29][30][31][32][33].…”
Section: Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nle acts in large ribosomal subunit in yeasts, 20,21 fungi, 36 plants 37 and mammals. 23 Contrary to Drosophila, 38 Nle loss of function does not seem to interfere with the Notch pathway in the mouse hematopoietic 23 and intestinal (this study) lineages.…”
Section: Discussionmentioning
confidence: 99%
“…Its ortholog in yeast, Rsa4, was shown to be essential for the late step of maturation and subsequent export of the 60S particle. [20][21][22] We recently showed that Nle role in the maturation of the large ribosomal subunit is conserved in mouse and that Nle is required for the maintenance of hematopoietic stem cells. 23 During the course of this study, we noticed that the gut was also sensitive to Nle deletion.…”
mentioning
confidence: 99%